2016
DOI: 10.2967/jnumed.116.176156
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Task-Specific Glucose Metabolism with Constant Infusion of18F-FDG

Abstract: The investigation of cerebral metabolic rate of glucose (CMRGlu) at baseline and during specific tasks previously required separate scans with the drawback of high intrasubject variability. We aimed to validate a novel approach to assessing baseline glucose metabolism and task-specific changes in a single measurement with a constant infusion of 18 F-FDG. Methods: Fifteen healthy subjects underwent two PET measurements with arterial blood sampling. As a reference, baseline CMRGlu was quantified from a 60-min sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 39 publications
7
112
0
Order By: Relevance
“…Given that the BOLD-fMRI signal indexes recent neural activity with a temporal resolution of 0.5-3 s, there is a significant temporal confound when comparing simultaneously acquired FDG-PET and BOLD-fMRI activation maps. Comparable results were recently obtained by (Hahn et al, 2016) in the motor cortex. One procedure is to dynamically track FDG uptake by slowly infusing FDG over the course of the scan.…”
Section: Simultaneous Bold-fmri/fdg-pet Imagingsupporting
confidence: 83%
See 1 more Smart Citation
“…Given that the BOLD-fMRI signal indexes recent neural activity with a temporal resolution of 0.5-3 s, there is a significant temporal confound when comparing simultaneously acquired FDG-PET and BOLD-fMRI activation maps. Comparable results were recently obtained by (Hahn et al, 2016) in the motor cortex. One procedure is to dynamically track FDG uptake by slowly infusing FDG over the course of the scan.…”
Section: Simultaneous Bold-fmri/fdg-pet Imagingsupporting
confidence: 83%
“…In a proof-of-concept study, Villien et al (2014) demonstrated that a slow continuous infusion technique yields sufficient FDG-PET signal in the occipital cortex during a checkerboard stimulation to be able to identify activation in the primary visual cortex. Comparable results were recently obtained by (Hahn et al, 2016) in the motor cortex.…”
Section: Simultaneous Bold-fmri/fdg-pet Imagingsupporting
confidence: 83%
“…Using GLM, the FDG time activity signal can be modelled as a linear combination of a baseline metabolic signal and a task induced activation signal. The baseline represents a glucose measure that is independent of any task stimulation, and the activation signal is defined as the task induced FDG activity changes (Hahn et al 2016;Villien et al 2014 , which includes head motion, physiological noise and other noise terms. These design matrices incorporate a priori knowledge to parameterize the linear model.…”
Section: Glm Of Fpet Datasetsmentioning
confidence: 99%
“…The aim of the fPET approach is to maintain a continuous plasma supply of FDG to provide improved sensitivity of brain-state changes, and better temporal dynamics than bolus PET to track dynamic change of glucose uptake over time. Several studies have demonstrated that fPET can isolate task related changes in glucose uptake (Hahn et al 2016;Hahn et al 2018;Rischka et al 2018;Villien et al 2014;Jamadar, Ward, Carey, et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation